HEART HISTOPATHOLOGY CHANGES OF WHITEWISTAR RATS SATISFIED WITH CHRONIC APPICAL PERIODONTITIS POST ADMINISTRATION OF GREEN MENIRAN LEAF ETHANOL EXTRACT IN CALCIUM HYDROXIDE AND 2% CHLORHEXIDIN DIGLUCONATE AS ROOT CANAL MEDICAMENT PASTE - Komang Hendry Wibawa Pramartha; Luh Made Sudimartini; Anak Dharmayudha; Ni Kadek Eka Widiadnyani (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Periodontitis is a disease that affects cats and dogs, which the herbal medicine that is used to treat periodontitis, namely meniran. Meniran is used as pain reliever and has antioxidant, anti-inflammatory properties, and antibacterial. The aim of this research was establishing the allotmen of ethanol extract of green meniran leaves on the histopathological features of the heart of Wistar rats with chronic apical periodontitis. This research of laboratory experiment was using the control of group desgn posttest randomly that conducted in several stages. Four groups was made for the test subjects that is consisting of 12 rats each, and each group was tested and divided into 3 groups. Each rat was dissected from one heart preparation in five microscopic fields of view. The analyzed data was the rat heart that is examined histopathologically to see if there is necrosis and congestion. In addition, the analysis was actualized by concerning the effect of the ethanol extract in green meniran leaves that was gived to histopathology of the heart utilizing the non-parametric statistical test, namely Kruskal-Wallis. The Kruskal-Wallis analysis resulted that treatment using ethanol extract of green meniran leaves had an effect on relieving necrosis (p<0.05) and congestion (p<0.05) in the heart organ, which means better than control group. Based on the result, the conclusion was obtained that the distribution of ethanol extract in green meniran can improve the histopathology of the heart of Wistar rats towards normal as seen from a decrease in congestive lesions and necrosis, especially in K3 given calcium hydroxide, 2% chlorhexidine digluconate and 10% of ethanol extract of green meniran. The future research need to inspect the impact of giving a combination of calcium hydroxide, 2% chlorhexidine digiluconate and 10% of ethanol extract green meniran in the long term.